Oxidative and Molecular Responses in Capsicum annuum L. after Hydrogen Peroxide, Salicylic Acid and Chitosan Foliar Applications - Mejía-Teniente, Laura (Molecular Diversity Preservation International (MDPI), 2013)
Hydrogen peroxide (H(2)O(2)) is an important ROS molecule (Reactive oxygen species) that serves as a signal of oxidative stress and activation of signaling cascades as a result of the early response of the plant to biotic stress. This response can also be generated with the application of elicitors, stable molecules that induce the activation of transduction cascades and hormonal pathways, which trigger induced resistance to environmental stress. In this work, we evaluated the endogenous H(2)O(2) production caused by salicylic acid (SA), chitosan (QN), and H(2)O(2) elicitors in Capsicum annuum L. Hydrogen peroxide production after elicitation, catalase (CAT) and phenylalanine ammonia lyase (PAL) activities, as well as gene expression analysis of cat1, pal, and pathogenesis-related protein 1 (pr1) were determined. Our results displayed that 6.7 and 10 mM SA concentrations, and, 14 and 18 mM H(2)O(2) concentrations, induced an endogenous H(2)O(2) and gene expression. QN treatments induced the same responses in lesser proportion than the other two elicitors. Endogenous H(2)O(2) production monitored during several days, showed results that could be an indicator for determining application opportunity uses in agriculture for maintaining plant alert systems against a stress.